The great escape health, wealth, and the origins of inequality - Deaton, Angus (Blackstone Audio, 2016)
The world is a better place than it used to be. People are wealthier and healthier, and live longer lives. Yet the escapes from destitution by so many have left gaping inequalities between people and between nations. In The Great Escape, Angus Deaton--one of the foremost experts on economic development and on poverty--tells the remarkable story of how, starting two hundred and fifty years ago, some parts of the world began to experience sustained progress, opening up gaps and setting the stage for today's hugely unequal world. Deaton takes an in-depth look at the historical and ongoing patterns behind the health and wealth of nations, and he addresses what needs to be done to help those left behind. Deaton describes vast innovations and wrenching setbacks: the successes of antibiotics, pest control, vaccinations, and clean water on the one hand, and disastrous famines and the HIV/AIDS epidemic on the other. He examines the United States, a nation that has prospered but is today experiencing slower growth and increasing inequality. He also considers how economic growth in India and China has improved the lives of more than a billion people. Deaton argues that international aid has been ineffective and even harmful. He suggests alternative efforts--including reforming incentives to drug companies and lifting trade restrictions--that will allow the developing world to bring about its own Great Escape. Demonstrating how changes in health and living standards have transformed our lives, The Great Escape is a powerful guide to addressing the well-being of all nations
Keywords: Income distribution